2014
DOI: 10.1039/c3nr05462d
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell force spectroscopy of pili-mediated adhesion

Abstract: Although bacterial pili are known to mediate cell adhesion to a variety of substrates, the molecular interactions behind this process are poorly understood. We report the direct measurement of the forces guiding pili-mediated adhesion, focusing on the medically important probiotic bacterium Lactobacillus rhamnosus GG (LGG). Using non-invasive single-cell force spectroscopy (SCFS), we quantify the adhesion forces between individual bacteria and biotic (mucin, intestinal cells) or abiotic (hydrophobic monolayers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
79
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 42 publications
13
79
0
2
Order By: Relevance
“…This mechanical resilience results from strategically located intramolecular isopeptide bonds (29). AFM demonstrated that pili from the probiotic Lactobacillus rhamnosus GG bacterium exhibit nanospring properties (37). The pilus spring constant measured at high force (>500 pN) was 15 pN nm −1 and was thus similar to the Cna value.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanical resilience results from strategically located intramolecular isopeptide bonds (29). AFM demonstrated that pili from the probiotic Lactobacillus rhamnosus GG bacterium exhibit nanospring properties (37). The pilus spring constant measured at high force (>500 pN) was 15 pN nm −1 and was thus similar to the Cna value.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the loading rate and contact time enabled researchers to assess the kinetic dissociation and association constants of the bonds. Using SCFS, Sullan et al (108) investigated the forces guiding pili-mediated adhesion in probiotic L . rhamnosus GG (LGG) bacteria.…”
Section: Functional Insightsmentioning
confidence: 99%
“…With this method, the forces driving pili-mediated adhesion between individual bacteria and different types of surfaces (biotic surfaces and abiotic surfaces) were measured. 131 The results revealed that adhesion forces strongly depended on the nature of the target substrate. Besides, the adhesion involved two different mechanical responses.…”
Section: Single-cell Force Spectroscopymentioning
confidence: 90%
“…Besides, the nanoscale forces engaged in the physiological processes of yeasts, including yeast flocculation 137 and yeast-macrophage adhesion, 138 have been investigated, improving our understanding of yeast adhesions. All together, these studies [128][129][130][131][132][133][134][135][136][137][138] allow directly quantifying adhesion interactions between individual microbial cells, opening up new avenues for understanding how cell surfaces respond to mechanical forces and how these responses are used to guide cell surface interactions.…”
Section: Single-cell Force Spectroscopymentioning
confidence: 99%